(untitled) (Numerus academy review, 2026)
The development of cross-border international trade operations and the inadequacy of national laws for settling disputes arising from them, constituted an inevitable necessity to search for a more specialized technical tool to resolve these disputes away from the national judiciary of the state, which is what the Algerian legislator tried to devote within the Civil and Administrative Procedures Law through the provisions of commercial arbitration. International to ensure the settlement of international trade disputes. Where this study aims to reveal the most effective solutions to resolve this type of disputes through arbitration to ensure the speed of their settlement in light of their privacy, as well as the scope of judicial intervention in that.